2020
DOI: 10.21107/agriscience.v1i1.7505
|View full text |Cite
|
Sign up to set email alerts
|

Efisiensi Ekonomi Usahatani Jagung Lokal Di Pulau Madura

Abstract: Jagung merupakan komoditas yang prospektif sebagai pangan pokok kedua setelah padi. Harga jagung lokal Madura lebih tinggi dibandingkan harga jagung varietas lain. Penggunaan input produksi yang belum sesuai menyebabkan produktivitas rendah dan penggunaan biaya yang tinggi. Penelitian bertujuan untuk menganalisis tingkat efisiensi teknis, alokatif dan ekonomi usahatani jagung lokal di Pulau Madura. Penelitian dilakukan di empat kabupaten dengan 60 responden yang ditentukan secara purposive. Berdasarkan hasil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…Researchers also found that many corn farmers in East Java still use traditional cultivation technologies, such as local corn seeds and rain-fed water systems. The two findings in the preliminary research in previous research also influenced productivity, efficiency and income [8][9][10]. The emergence of the problem of decreasing productivity and corn production has also worsened the demand and supply of corn production in East Java.…”
Section: Introductionmentioning
confidence: 94%
“…Researchers also found that many corn farmers in East Java still use traditional cultivation technologies, such as local corn seeds and rain-fed water systems. The two findings in the preliminary research in previous research also influenced productivity, efficiency and income [8][9][10]. The emergence of the problem of decreasing productivity and corn production has also worsened the demand and supply of corn production in East Java.…”
Section: Introductionmentioning
confidence: 94%
“…Due to the hot weather conditions and low water availability in Madura, people have opted for food crop farming on dry land (Anam et al, 2020). Corn is the most suitable crop for cultivation in Madura's dry land (D. D. Prasetyo & Fauziyah, 2020). The advantage of local corn from the Madura region is its shelf life of around one year, making it a reliable food reserve (Amzeri, 2018).…”
Section: Farmers' Solutions To Resolve Tobacco Marketing Conflictsmentioning
confidence: 99%
“…Kelebihan dari fungsi produksi Cobb-Douglas yaituadanya kemudahan untuk dianalisis dibanding fungsi yang lain, yang mana koefisien regresi menampilkan elastisitas produksi, sedangkankadar elastisitas menampilkan besarnya tingkat nilai return of scale (Soekartawi, 2003). Bentuk umum dari fungsi produksi Cobb-Douglas yaitu: Menurut Prasetyo & Fauziyah (2020), efisiensi merupakan perbandingan antara input dan output yang berkaitan dengan berbagai jumlah penggunaan input dan jumlah maksimum output yang dapat dihasilkan.Terminologi ilmu ekonomi menjelaskan bahwa pada dasarnya makna efisien terbagi menjadi 3 macam, yaitu: (1) efisiensi alokatif, (2) efisiensi teknis, dan (3) efisiensi ekonomi. Menurut Ngenoh et al (2015), efisiensi teknis dari seorang produsenbiasanya digunakan sebagai wadah dalam memberikan beberapa informasi yang diperlukanoleh petani agar dapat mengatasi permasalahan produktivitas rendah.…”
Section: Tinjauan Pustakaunclassified